Verbalization of the concept of "beauty" in the phraseological units and proverbs of the Erzya and Finnish languages - Karpunina, Ekaterina Dmitrievna; Mosina, Natalya Mikhaylovna (Этническая культура, 2024)
The growing interest in concepts in cognitive linguistics highlights the relevance of studying the concepts of beauty in different cultures. The purpose of the article is to study the semantic features of the expression of this concept in the Erzya and Finnish languages based on a comparative analysis of phraseological units and paroemias. The concept of beauty is universal, and its perception and evaluation vary depending on cultural and social factors, which makes its analysis important for understanding the worldview of two distant peoples. The material for the study was phraseological units and paroemias representing the concept of "beauty", obtained as a result of using the continuous sampling method from specialized dictionaries and collections. The study showed that the verbalization of beauty in the analyzed languages reflects a multifaceted attitude to this concept. Based on a common semantic feature, we have identified four groups of phraseological units and paroemias describing external and internal beauty, deceptive properties of beauty, as well as a critical attitude to appearance. The etymological analysis of the basic lexemes was also carried out during the study. The article demonstrates that the concepts of beauty in the Erzya and Finnish languages not only differ, but also illustrate the unique cultural values of the two peoples. The results of the work can be useful for teaching Finno-Ugric languages, as well as for ethnolinguistic research and intercultural communication.